EXPLORING DOCTORAL SUPERVISION IN LAW EDUCATION: PERSPECTIVES IN TEACHING AND PEDAGOGY - Tasnim Ahmed (Malaysian Journal of Learning and Instruction)
Purpose - This paper explores the pedagogical practices employed in supervising law PhD students within law schools. The study adopts an auto-ethnographic approach to investigate the beliefs of both supervisors and students regarding teaching, learning, research and supervision.